Pengaruh Pembelajaran IPA Berpendekatan Culturally Responsive Teaching Tema Batik Sekar Sari Sandeyan terhadap Pemahaman Konsep dan Sikap Peduli Budaya - Alfita Marhaeningtyas; Insih Wilujeng (PT. Komunitas Peneliti Alinea, 2026)
This study aims to (1) determine the differences in students' conceptual understanding and cultural awareness attitudes between science learning using the Culturally Responsive Teaching (CRT) approach on the theme of Batik Sekar Sari and science learning using the scientific approach, (2) determine the effect of science learning using the Culturally Responsive Teaching (CRT) approach on the theme of making Sekar Sari Sandeyan batik and science learning using the scientific approach on students' conceptual understanding and cultural awareness attitudes. This type of research is a quasi-experimental research design with a pretest-posttest control group. The research instruments used were conceptual understanding questions, cultural awareness attitude questionnaires, and learning implementation observation sheets. Data analysis techniques used were normality tests, homogeneity tests, correlation tests, MANOVA tests, and effect size tests The results of the study showed that (1) there were differences in students' understanding of concepts and attitudes of caring for culture between science learning using the CRT approach with the theme of Batik Sekar Sari and science learning using the scientific approach, (2) there was an influence of science learning using the CRT approach with the theme of Batik Sekar Sari on students' understanding of concepts and attitudes of caring for culture. Thus, the CRT approach that integrates culture can effectively improve science learning.